Improving Digital Competence of Tourism Academics and Professionals Through AI-Based Workshops in Indonesia and Vietnam - Tomy Andrianto; Nono Wibisono; Rivan Sutrisno; Eko Susanto; Abdul Malik Sayuti; Moch Yusup (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
The international community service program between Politeknik Negeri Bandung (Polban) and Duy Tan University (DTU) aims to strengthen the digital competencies of academics and tourism professionals in Indonesia and Vietnam. The program focuses on mapping digital transformation needs, conducting AI-based capacity-building workshops, and evaluating tourism courses syllabus toward digital readiness. Using survey data from 449 respondents analyzed through PLS-SEM, the results highlight self-readiness and system quality as key predictors of AI utilization in tourism education. The implementation included workshops in Vietnam (19 and 20 August 2025) emphasizing AI use among students for tourism analytics and digital content creation, and in Indonesia (October 2025) focusing on integrating AI applications into tourism courses. These collaborative initiatives bridge academic and industry gaps while promoting experiential learning and syllabus innovation, contributing to a more inclusive and sustainable digital tourism ecosystem in Southeast Asia.